A comparison of telbivudine and entecavir in the treatment of hepatitis B e antigen-positive patients: a prospective cohort study in China. (March 2016) - Zhang, Y.; Hu, P.; Qi, X.; Ren, H.; Mao, R.-C.; Zhang, J.-M.
Abstract: There are few studies directly comparing the efficacy and safety of telbivudine and entecavir. The present prospective cohort study aimed to evaluate the long-term efficacy and safety of these compounds in 196 hepatitis B e antigen (HBeAg)-positive patients with chronic hepatitis B for a median follow-up period of 172 weeks; 97 were treated with telbivudine and 99 were treated with entecavir. Patients showing suboptimal responses could also take adefovir at 24-48 weeks and all patients with viral breakthrough were started on adefovir. The 240-week cumulative proportions of patients showing undetectable hepatitis B DNA levels and serum alanine transaminase (ALT) normalization were similar in the two study groups. Viral breakthrough developed in 14% of the telbivudine group and in 2% of the entecavir group (p 0.002). Interestingly, the cumulative proportions of patients treated with entecavir and telbivudine showing HBeAg seroconversion were 12% versus 21% at 48 weeks (p 0.041), 15% versus 38% at 96 weeks (p 0.001), 24% versus 50% at 144 weeks (p 0.001), 33% versus 53% at 192 weeks (p 0.004) and 36% versus 53% at 240 weeks (p 0.005), respectively. Patients treated with telbivudine were therefore significantly more likely to show HBeAg seroconversion than those receiving entecavir and similar results were observed in study sub-groups matched for age, serum ALT, and HBV DNA levels. A safety analysis identified no differences between grade 3/4 creatine kinase elevations in the study groups and only telbivudine was associated with improved kidney function.